Detection and distribution of zoonotic pathogens in wild Norway rats (Rattus norvegicus) from Tehran, Iran. (July 2021) - Azimi, T.; Azimi, L.; Fallah, F.; Pourmand, M.R.; Peeri Dogaheh, H.; Rafiei Tabatabaei, S.
Abstract: This is the first study on the prevalence of vector-borne zoonotic pathogens found in Rattus norvegicus ( R. norvegicus ) in urban areas of Tehran, Iran. Serological tests were used to detect IgG antibodies against Coxiella burnetii ( C. burnetii ) and Rickettsia spp. using a commercial qualitative rat ELISA kit. The frequency of Streptobacillus moniliformis ( S. moniliformis ) and Bartonella spp. was determined using a conventional PCR method. Molecular detection and characterization of Leptospira spp. were conducted using TaqMan real-time PCR based on lipL32 gene and SecY typing methods. A total of 100 R. norvegicus rats were collected from five regions in Tehran, Iran, and investigated to determine their zoonotic pathogens. S. moniliformis and Bartonella spp. were detected in 23 of 100 (23%) and 17 of 100 (17%) R. norvegicus populations, respectively. The highest prevalence of S. moniliformis and Bartonella spp. with similar frequency rates (n = 6/20; 30%) was seen among the R. norvegicus rats captured from the northern and southern parts of Tehran, respectively. Seroreactivity against C. burnetii and Rickettsia spp. was detected in 4% and 1% of R. norvegicus, respectively. C. burnetii. was identified only in one rat captured from the eastern part of Tehran. Results showed that Leptospira spp. was detected only in two rats, collected from the southern part (n = 2/20; 10%) of Tehran. The secY typing method identified two different Leptospira species including L. interrogans and L. kirschneri. The results showed that urban rats might play an important role in transmission of zoonotic pathogens to humans.